N01 Does physical activity positively impact fatigue in individuals with Inflammatory Bowel Disease?. (27th May 2021) - Farrell, D; Bager, P; Bredin, F; Cairnes, V; Forry, M; Gilham, E; Godwin, N; Herdmangrant, R; Ni Dhalaigh, D; O' Shea, T; Sugrue, K
Abstract: Background: Patients with Inflammatory Bowel Disease (IBD) often experience the problematic and burdensome symptom of fatigue, both during periods of relapse and remission. The optimal management of fatigue in IBD is uncertain, however there is evidence suggesting that physical activity is likely to be a beneficial way of managing the symptom. The aim of this study is to explore the relationship between fatigue and objective measurements of both physical activity metrics and varying intensities of physical activity for individuals with IBD. Methods: A multi-centred, European, cross-sectional, correlational study was employed. A consecutive sample of 187 patients with Crohn's disease (59%) or ulcerative colitis (41%) were recruited from six IBD centres in the Republic of Ireland (42%), United Kingdom (40%) and Denmark (18%). Fatigue was measured using the IBD-Fatigue (IBD-F) scale, including both the level of fatigue (IBD-F, Section 1) and impact of fatigue (IBD-F, Section 2). Physical activity was objectively measured using scientifically validated triaxial accelerometers (ActiGraph wGT3X-BT) during seven consecutive days. Results: A moderate level of fatigue (IBD-F Section 1 Md (IQR) = 10 (6 – 13)), predominantly intermittent in nature (72%) was reported by participants (57.4% female; 59% Crohn's disease; 43% active disease). Participants self-reported sleeping an average of 8.7 hours over the seven nights. During the week, the intensity of activity was predominantly sedentary (Md 5 days, 22 hours, 20 minutes) or light (Md 19 hours, 35 minutes). The median moderate-to-vigorous intensity of physical activity per day was 32.2 minutes and step count over the week was 47052 steps. There was no evidence of a unique linear or non-linear relationship between each of the objective measurements of physical activity with IBD-related fatigue. This lack of evidence extended separately to patients in remission and to patients with active disease. These findings are in the context of a statistically significant moderately-strong relationship between disease activity (measured using both HBI and SCCAI) and level of fatigue for both patients of Crohn's disease (rs = .327, p = .001, n = 96) and ulcerative colitis (rs = .353, p = .003, n = 71). Conclusion: This large multi-centred study shows no association between objective measurements of physical activity and IBD-fatigue. These findings suggest that engaging or not engaging in physical activity has no differential impact on self-assessment of fatigue.